2017
DOI: 10.1002/eco.1866
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation responses to an ecological water conveyance project in the lower reaches of the Heihe River basin

Abstract: The lower reaches of the Heihe River basin (HHLR), which is located in arid and semiarid areas of Northwest China, has experienced severe environmental deterioration in the past several decades. The ecological water conveyance project was initiated by the Chinese Government in 2000 to address this degraded ecosystem. In this paper, runoff, vegetation changes, and the relationship between runoff and vegetation in different regions were explored after the project, normalized difference vegetation index (NDVI), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The normalized difference vegetation index (NDVI) is a commonly used indicator for evaluating vegetation development. Landsat NDVI data have been widely used for studying changes in regional ecological environments [8,19,20,[41][42][43]. In general, NDVI values range between −1 and 1.…”
Section: Study Areamentioning
confidence: 99%
“…The normalized difference vegetation index (NDVI) is a commonly used indicator for evaluating vegetation development. Landsat NDVI data have been widely used for studying changes in regional ecological environments [8,19,20,[41][42][43]. In general, NDVI values range between −1 and 1.…”
Section: Study Areamentioning
confidence: 99%
“…Similarly, in the Heihe River Basin in north‐western China, time lag responses to runoff varied in different regions. Regions where runoff was lower showed higher time lag responses, as well as the timing in runoff had different effects, along with spring flows that favoured germination versus autumn flows that favoured growth during the next year (Zhang, Ye, Chen, & Zu, ). In our study, most of the pulse flow infiltrated into the regional aquifer by the end of the 2014 growing season (Kennedy et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the area of floodplain forest has reached an overall area of 1.0 × 10 5 ha. The EWCP has become a national and global model of successful restoration for damaged natural environments in arid areas (Halik et al, ; Halik et al, ; Huang et al, ; Guo et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring over many years has shown that the annual precipitation of the study area ranged from 17.4 to 42.0 mm with a total potential annual evaporation of 2,600–3,200 mm. The flora of the study area can be divided into 14 families, 24 genera, and 40 species of vascular plants (Zhang, Ye, Chen, & Xu, ).…”
Section: Introductionmentioning
confidence: 99%